Pediatric visceral leishmaniasis in Tartous, Syria - Ali Othman Hamwi (Thieme Medical and Scientific Publishers Pvt. Ltd., 2020)
Background: Visceral leishmaniasis (VL) type in Syria is Lashmania infantum, a fatal incapacitating disease, which is mostly seen in infants. Subjects and Methods: Hospital records of 19 children with VL were retrospectively reviewed. The period of the study was from June 2016 to July 2019. Results: The median age of the patients was 45.5 months. None was coinfected with human immunodeficiency virus or known to be immunocompromised. Pallor and anemia were observed in all cases, fever in 13 (68.42%), splenomegaly in 18 (94.7%), hepatomegaly in 11 (57.9%), thrombocytopenia in 15 (78.95%), and leukopenia in nine (47.4%). A bone marrow aspirate was obtained and Leishmania amastigotes were detected in all patients. All patients were initially treated with meglumine antimonate; one child did not respond and was treated with lipid formulations of amphotericin B. Conclusions: Presentation of VL in the pediatric age group is characterized by pallor, fever, splenomegaly, and hepatomegaly. Hematological and biochemical indices are typical with cytopenias. In all cases, microscopic examination provided a positive diagnosis. Despite recent reports on decreased responses to antimonial drugs of patients with Mediterranean VL, meglumine antimonate treatment appears to be still highly effective in Syria.